The photolysis and radiolysis of barium azide, with some observations on the photolysis and radiolysis of lithium azide - Sears, William George (Department of Chemistry, 2024)
[Many pages missing] If the respective curves lntersect and the excited state has a minimum lying inside the ,ground state curve, then on optical transition to the excited state wi II be followed by a radiationless transition to the point where the excited and ground state curves intersect. If, however, the minimum in the potential energy curve lies outside the potential energy of the ground state, an electron could remain in the excited state until a radiationless transition occursg This would then correspond to a metastable stateo.